Pengaruh Konser Blackpink “Bornpink World Tour In Jakarta 2023” Terhadap Gaya Busana Penonton - Ratu Balqis; Asep Miftahul Falah (ATRAT: Jurnal Seni Rupa, 2025)
In Indonesia, K-Pop music concerts have become highly anticipated and sought-after events by fans of South Korean idols. Blackpink is a popular K-Pop group that has successfully captured the attention of audiences from various backgrounds. This study aims to investigate the influence of the Blackpink concert “Bornpink World Tour Jakarta 2023” on the fashion style of the audience. This research employs a qualitative method with a phenomenological approach, and data collection is conducted through interviews with two respondents who attended the Blackpink concert in Jakarta and analysis through social media regarding public reactions to the concert. The results of the interviews indicate that the Blackpink concert has a significant impact on changes in the audience’s fashion style. Blackpink fans who attended the concert were inspired by the fashion style of the Blackpink members and thus chose fashionable and daring outfits when attending the concert. The fashion style of the Blackpink members serves as inspiration for the audience to experiment with significantly different and unique fashion styles compared to their usual choices. This is influenced by factors such as idol identification, fashion trends, and self-expression. The study concludes that the Blackpink concert has a positive impact on the fashion style of the audience, allowing them to express themselves more freely. The findings of this research can be referenced to understand that K-Pop music events influence fashion trends and clothing culture in Indonesia.